2008
DOI: 10.1007/s12291-008-0027-1
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition of genetic polymorphism with the risk of urolithiasis

Abstract: Urolithiasis is a relevant clinical problem with a subsequent burden for health system. The aim of this review is to provide recent progress made using genetic polymorphisms to define pathophysiology, to identify persons at risk for kidney stone disease and to predict treatment response. Population case-control studies are useful both as an alternative and an adjunct as compared to family studies. These involve either whole genome scanning or candidate gene approaches. While whole genome scanning is likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…One SNP of interest is the ApaL1 C/T SNP located at the 3′-untranslated region (UTR) of the urokinase gene on chromosome 10 [2]. It has been proposed that the fibrinolytic function of urinary urokinase may prevent the formation of organic matrix in the urinary tract [3], a major step in urinary stone formation [4]. Another candidate gene is the vitamin D receptor (VDR) Abstract The purpose of this study was to determine differences in genotype distribution and allele frequency of urokinase and vitamin D receptor (VDR) single nucleotide polymorphisms (SNPs) between first-stone formers, recurrent stone formers, and controls in a Caucasian population.…”
Section: Introductionmentioning
confidence: 99%
“…One SNP of interest is the ApaL1 C/T SNP located at the 3′-untranslated region (UTR) of the urokinase gene on chromosome 10 [2]. It has been proposed that the fibrinolytic function of urinary urokinase may prevent the formation of organic matrix in the urinary tract [3], a major step in urinary stone formation [4]. Another candidate gene is the vitamin D receptor (VDR) Abstract The purpose of this study was to determine differences in genotype distribution and allele frequency of urokinase and vitamin D receptor (VDR) single nucleotide polymorphisms (SNPs) between first-stone formers, recurrent stone formers, and controls in a Caucasian population.…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility genes for stone disease are the VDR gene, calcitonin receptor gene, interleukin 1 gene cluster, urokinase gene, arginine p21, VEGF, AR&ER receptor, and e-cadherin gene. 17 The most popular is the VDR gene, which is 5.6 kb in size and is located on chromosome 12q12-14. VDR is related to genomic and non-genomic effects of 1.25(OH)D on renal tubular cells and modulates citrate metabolism and transport of calcium and phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage disequilibrium is the nonrandom association of alleles at linked loci and is required to assess genes predisposition to complex diseases, such as urolithiasis. 17,20,21 Many studies have shown that VDR gene polymorphism has an undeniable relationship with urolithiasis and hypercalciuria. Hypercalciuria may result from increased calcium absorption and decreased renal calcium or phosphorus reabsorption and/or enhanced bone demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…28 For the CALCR gene c.1340T.C; rs1801197 variant, the genotypes were determined as previously described. 29 For the VDR c.1024+283G.A; rs1544410 gene variant, we used a protocol described by Kaya et al 30 The PCR reactions were prepared in a 25 Thermo Fisher Scientific). The digestion products were resolved in 3% high-resolution agarose gel electrophoresis (MetaPhor, Lonza, Basel, Switzerland) and stained with RedSafe (Chembio Ltd, Rickmansworth, UK) for visualization on a UV transilluminator.…”
Section: Bmd Assessmentmentioning
confidence: 99%